AN ANALYSIS OF NOUNS AND VERBS USED IN SELECTED ONLINE FABLES - Rueangsanam, Sunant; Dennis, Nutprapha K. (International Journal of Research -GRANTHAALAYAH, 2017)
This study analyzed parts of speech found in forty Aesop’s fables with specific attention to the categories and frequencies of nouns and verbs used. This study aimed to analyze the most used of nouns and verbs in the stories. The material used in the forty selected Aesop’s fable from the website entitled http://www.bbc.co.uk. An analysis of the types of words was done using the program entitled https://open.xerox.com as an instrument for collecting data. The statistics used in data collection was percentage. The results of the study showed that there were two types of nouns and two types of verb in the selected Aesop fables. “Common Nouns” was the most commonly used with a frequency of 95.47%, and “action verbs” were the most commonly used with a frequency of 83.62%. Furthermore, “gerund” was also found in these Aesop fables. Comprehending types of words will help strengthen reading efficiency, reduce confusion of words usage as well as for readers to fully enjoy reading.